Sensitivity of Ribonucleic Acid and Deoxyribonucleic Acid Viruses to Different Species of Interferon in Cell Cultures - Youngner, Julius S. (1972)
Although two deoxyribonucleic acid (DNA) viruses, pseudorabies (PsRV) and vaccinia, are as susceptible as a ribonucleic acid (RNA) virus, vesicular stomatitis (VSV), to interferon when tested in chicken or mouse cells, they are refractory to inhibition in interferon-treated primary rabbit kidney cells and in a continuous line (RK-13) of rabbit kidney cells. Superinfection with VSV of RK-13 cells first infected with PsRV completely blocks the replication of PsRV with no effect on VSV yield. When the same experiment is carried out in RK-13 cells pretreated with 1,000 units of interferon, VSV replication is inhibited, which permits PsRV to replicate normally. These findings demonstrate that in the same cell one virus (PsRV) can be refractory to interferon and a second virus (VSV) can be susceptible. These experiments show that rabbit kidney cell cultures are deficient in the synthesis of resistance factors active against the DNA viruses tested and raise the possibility that separate resistance factors may exist for RNA and DNA viruses. In the case of sequential infection of interferon-treated RK-13 cells with vaccinia and VSV, it was found that not only was vaccinia replication refractory to inhibition by interferon, but also that prior infection with vaccinia was able to partially reverse the effect of the inhibitor on the replication of the VSV used for superinfection. On the basis of these and other data it is postulated that a vaccinia virion component or a replication product of vaccinia virus, or both, enables VSV to escape the inhibiting action of interferoninduced resistance factors.